Dynamic Modeling and Optimization of Cryogenic Air Separations Units: Design and Operation Strategies - Cao, Yanan (My University, 2016)
In the air separation industry, cryogenic distillation is the dominant technology for separating large quantities of air into individual high purity component products. Due to the complexity of the process, in addition to significant energy input, air separation units (ASUs) also have high degrees of material and thermal integration and low process agility. As markets become more competitive and dynamic, especially after electricity market deregulation, ASUs can no longer practice mostly stationary operations, and are in need for design and control strategies to achieve high adaptability. In this study, we address such issues through a dynamic optimization framework. The use of rigorous dynamic models is important for developing economically beneficial designs and operating practices. The first part of this study focuses on the modeling aspect. For the column section of the plant, a full-order stage-wise model and a collocation based reduced order model are proposed. Model size, simulation time and predication accuracy are compared. For the primary heat exchanger, a novel moving boundary model is derived to handle the phase change in such a multi-stream heat exchanger. Simulation results demonstrate the capability of the proposed model in tracking the boundary points of the phase change occurrence, as well as the potential pinch point, along the length of the heat exchanger. The second part of the study addresses the operation aspects of ASUs through conducting dynamic optimization studies with collocation based dynamic models. We first performed a comprehensive analysis for a storage-then-utilization strategy on a nitrogen plant, following a two-tier multi-period formulation. As the parameter varies with time, the plant collects liquid, either directly from liquid product or by liquefaction of overproduced gas product, and then redistributes it for meeting gas product demand or as additional reflux. Effects of electricity price and demand profiles, additional operation costs, as well as product specifications are explored. Then we investigated the economic incentive for employing preemptive actions on a super-staged argon system, which allows the plant to take actions before external changes arrive. In the evaluation, changes are in the gas oxygen product demand. During the preemptive period, the plant takes either a single set or multiple sets of control actions. In the demand increase case, operation degrees of freedom are introduced to or removed from the set of decision variables. The demand decrease scenarios are explored with an under-supplied or saturated liquid oxygen market.
Dynamic Modeling and Optimization of Cryogenic Air Separations Units
Support for this work from Praxair; the McMaster Advanced Control Consortium; and the Natural Sciences and Engineering Research Council of Canada (NSERC), Grant CRDPJ 445717, is gratefully acknowledged.
Keywords: dynamic modeling; dynamic optimization; distillation; multi-stream heat exchanger; air separation units; collocation based model reduction; operation and design; demand response; chemical process; time varying market; storage-then-utilization; multi-period, multi-tiered; moving boundary